Circular cities: Challenges in adaptation of new waste management strategies - Ozturk, Irem; Topuz, Emel (Nova Science Publishers, Inc., 2021)
On the planet where consumption is increasing day by day, limited resources are compelling to build a sustainable future. According to the estimations of United Nations, life in cities will be more common, with 66% of the population residing in cities, and the global footprint will triple by 2050. These statistics indicate that there will be an enormous resource shortage if no action is taken for waste recycle/recovery/reuse in cities. Moreover, results of over-consumption such as climate change are leading to precautions for food-water resilient cities. Due to these concerns, UNEP called countries for taking actions to reach sustainable development goals which were announced in 2015. The concept of circular city came to the agenda of countries for taking necessary actions. Regular (traditional) cities have linear flow of material and energy except for special efforts in local areas or in industrial sites whereas circular cities are developed in the context of circular flow of material and energy in city borders including urban regions to provide sustainable development. In circular cities, waste and wastewater is valorized and water, energy, and, materials (bioplastics, fertilizers, metal, protein-based food, building materials) are recovered from the waste and wastewater stream with appropriate technology choices. Therefore, waste management strategies requires to be adopted to this new concept of circular city. There are a number of technical, environmental, economic, human resources, social and regulatory challenges in ensuring the adaptation, and hence, the sustainability of waste management in circular cities. Inadequate and outdated infrastructure constitues a major obstacle to the application of sustainable technologies. Technically, a challenge circular cities face is that the all work accomplished still remains pilot or lab-scale. Sustainability of the market value of the recovered product demands more parameters such as processing, distribution and demand for the product after recovery. New technologies will bring new business areas and therefore qualified manpower will be required. It may take time for society to accept and adapt to change. This chapter aims to review potential challenges in adaptation of new waste management strategies through the transition period from linear cities to circular cities. © 2022 Elsevier B.V., All rights reserved.